Prevalensi Hasil Uji Saring Hbsag Pada Darah Donor Di Unit Tranfusi Darah (UTD) PMI Sampang Madura - Rahma Widyastuti; Nur Vita Purwaningsih; Ellies Tunjung Sari Maulidiyanti; Tri Ade Saputro (Universitas Muhammadiyah Surabaya, 2022)
The screening blood test is a stage that is carried out by each PMI to ensure the safety before blood transfusion. It is usually done on antibodies (Ab) such as anti-HCV, anti-HIV, TPHA or antigen (Ag) such as HBsAg. HBsAg is the outer coat protein of hepatitis B virus (HBV) and a sign that the individual has been infected with the hepatitis B virus. Hepatitis B virus can cause acute problems and even cirrhosis of the liver. One of the screening blood test methods which is used to detect hepatitis B is ELISA (Enzyme Linked Immuno Sorbent Assay) method. This research was conducted at UTD PMI Sampang by using the data collection in February 2020, and aimed to find out the overview of HBsAg examination results on the screening blood test using ELISA method based on age and sex. Based on the screening blood test, 9 people (3%) were reactive HBsAg and 345 people (97%) were non-reactive. In the age category, the highest number of reactive HBsAg donors was in the age group of 18-24 years old, that was 4 donors (1.1%), while the highest number of non-reactive HBsAg donors was in the age group of 25-44 years old, that was 184 people ( 51.9%). In the gender category, donors with the most reactive HBsAg results were male, that was 8 people (2.3%) and donors with the highest non-reactive HBsAg results was male, that was 283 people (79.9%). In order to minimize hepatitis B, it is expected that society should avoid activities which can cause hepatitis B infection. Keywords : HBsAg, Blood Transfusion, Screening Blood Test